Menstrual awareness, hygiene, practices and perceptions among the adolescent girls of Nahan, Himachal Pradesh, India - Kaur, Maninder; Vats, Tanya (International Journal Of Community Medicine And Public Health, 2020)
Background: Onset of first menstrual cycle also termed as “menarche” signifies the initiation of sexual maturation of girls. The present study aims to represent an amalgam of menstrual awareness, perceptions and hygiene in light of the associated menstrual practices prevalent in the adolescence girls of Nahan. Methods: A cross-sectional data of 189 girls aged between 10 to 16 years were collected from Nahan, district Sirmaur in Himachal Pradesh. Data regarding perceptions, awareness and hygienic conditions during menstruation were also gathered through an interview based schedule. Results: Menarche was known to be a normal physiological process by only 53.43% girls, while the rest of the participants didn’t know the reason for its occurrence. For 81.2% girls the informant was their mother and a very little role was played by sisters (5.36%), books (0.67%), friends (6.04%) and relatives (5.36%). Most of the girls (95.28%) used sanitary napkin as absorbent for menstrual flow, but the use of single sanitary napkin for 7 to 8 hours by 48% participants was of alarming concern. Stomachache was the most common problem associated with menarche, whereas breast heaviness (16.98%), body ache (16.03%) and backache (26.41%) were witnessed in considerable proportion of girls. A significant number of girls (78.3%) were prohibited from entering in the holy places/temples during this period. Conclusions: Although menarcheal health is acquiring greater significance across the globe, but the age old social restrictive practices associated with menstruation are still common and prevalent in this societies.